Penerapan Model Pembelajaran Bamboo Dancing Untuk Meningkatkan Hasil Belajar IPA Kelas IV Sekolah Dasar - Siti Khoirunisa’; Ismail Marzuki; Nanang Khoirul Umam (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
The application of the cooperative learning model of the bamboo dancing type in classroom action research with the aim of improving students' abilities which are expected to improve student learning outcomes in the cognitive shutter. This research was conducted in three cycles in grade IV UPT SD Negeri 83 Gresik, totaling 17 students with details of 8 girls and 9 boys. The data collection technique used observation sheets and also test questions, on the test sheet the questions consisted of 10 multiple choice questions and 5 description questions. The results of research on the application of this bamboo dancing learning model from cycles one to three always show a significant increase in learning outcomes, either classically or individually. The researcher concluded that the application of the bamboo dancing learning model succeeded in increasing the fourth grade science learning outcomes at UPT SD Negeri 83 Gresik. Keywords: learning model of bamboo dancing; learning outcomes.